Bang Rakam Model : A model for living life under flood problems. - Noidee, Mana; Kessornpatoom, Yuwachon; ThongKuod, Wasan; Bodeerat, Chot (Journal of Modern Learning Development, 2024)
When Bang Rakam had to become a water catchment area, there is heavy rain because the geography is lowland. The soil is sandy loam. Government agencies have therefore selected this area as a water retention area and divert water into the Bang Rakam Model area to slow down the drainage of water into the Nan Riverand Chao Phraya River reduce flooding problems in the capital cause the area to flood every year. Therefore, people must understand and apply knowledge in adapting to changes in various fields and coexist with the flooding conditions.That can able to maintain a sustainable way of life under flood problems.